2002
DOI: 10.1248/bpb.25.29
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Acylation of Somatostatin Analog with Long Chain Fatty Acids Enhances Its Stability and Anti-Proliferative Activity in Human Breast Adenocarcinoma Cells.

Abstract: The therapeutic potential of peptide drugs has remained unfulfilled due to the unfavorable physicochemical properties of these molecules. Peptides are extremely susceptible to proteolytic degradation in blood and tissues. The hydrophilic nature of peptides severely limits their permeability across hydrophobic cell membranes.2) RC-160, a potent somatostatin analog is one of the most extensively studied therapeutic peptides for its anti-proliferative and anti-secretory activity.D-Phe-Cys-Tyr-D-Trp-Lys-Val-Cys-Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 30 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…The activity of a compound in a biological system does not only depend on its interaction with cell membranes due to its lipophilicity but also on its affinity for specific cell receptors. For instance, Dasgupta et al [72] showed that in human breast cancer cells, the receptor affinity of somatostatin analogue was not affected by its acylation with palmitic acid, whereas this affinity was reduced when the peptide was acylated with stearic or butyric acids.…”
Section: Antiproliferative Activitymentioning
confidence: 99%
“…The activity of a compound in a biological system does not only depend on its interaction with cell membranes due to its lipophilicity but also on its affinity for specific cell receptors. For instance, Dasgupta et al [72] showed that in human breast cancer cells, the receptor affinity of somatostatin analogue was not affected by its acylation with palmitic acid, whereas this affinity was reduced when the peptide was acylated with stearic or butyric acids.…”
Section: Antiproliferative Activitymentioning
confidence: 99%
“…4 In recent years, several studies have suggested that SST functions as a tumor suppressor gene and possesses potent antitumor and antisecretory activity in several human cancers in vitro and in vivo. [5][6][7][8] Aberrant methylation of promoter CpG islands upstream of tumor suppressor genes is now well established as a major epigenetic mechanism of gene inactivation in tumorigenesis, 9 including ESCC and EAC. 10,11 More recently, data from our laboratory have shown that the SST promoter is methylated in 80% of human colon cancers, and that 5-aza-2 0 -deoxycytidine (5-Aza-dC) reverses SST promoter hypermethylation and restores SST mRNA expression in colon cancer cell lines.…”
Section: Conclusion Sst Promoter Hypermethylation Ismentioning
confidence: 99%
“…The lipidized form of somatostatin analogue RC-160 has previously been synthesized with one moiety of myristic acid (14 carbons) coupled to the N-terminal residue of RC-160 through a stable amide linkage. When tested in vitro, lipidized RC-160 showed increased stability and enhanced antiproliferation (8)(9)(10). However, no relevant in vivo results have been published so far.…”
Section: Introductionmentioning
confidence: 99%